The Influence of Financial Literacy and Sharia Financial Technology on Sharia Banking Products in Small and Medium Community Enterprises in the Sibolga Tapteng Region - Rica Rahim Lubis; Tuti Anggraini; Ahmad Perdana Indra (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: The purpose of this study is to analyze and determine the influence of financial literacy and Islamic financial technology on Islamic banking products in small and medium enterprises in the Sibolga Tapteng area Methods: This research method uses a quantitative approach, with a population of 30 people. The sample of this study amounted to 30 respondents. The Likert scale was used as a measurement tool in this study. Data collection was carried out through a questionnaire. Data analysis was carried out using multiple linear regression with the help of the SPSS 24 application. Results: Based on the results of the study, it shows that. The Financial Literacy variable (X1) is 0.325, which is positive. This means that Financial Literacy (X1) has a positive effect on Islamic Banking Products (Y). It is known that the t statistic or t count of Financial Literacy (X1) is 5.309> t table = 1.97 and the Sig. value is 0.000, which is t table = 1.97 and the Sig. value is 0.000, which is